Dysfunction of Tregs contributes to FGR pathogenesis via regulating Smads signalling pathway. Issue 6 (14th February 2020) - Xu, Yunzhao; Su, Min; Wang, Ziheng; Liu, Qinqin; Xu, Xiangyu; Gu, Shuting; Pan, Weidong; Ge, Wenliang
Abstract: Fetal growth restriction (FGR) is ranked number two of most common complication of abnormal pregnancy worldwide. The pathogenesis of FGR is complicated due to multiple aetiologies and the exact mechanism for FGR development is currently unknown. T regulatory cells (Tregs) are proven to play central roles in the maintenance of normal pregnancy. Peripheral blood samples of 102 pregnant human were collected analysed using flow cytometry to identify Tregs. We found that reduced Tregs and down‐regulation of Foxp3 were observed in peripheral blood of FGR patients. In FGR mouse model, we have found that Tregs were not only reduced in spleen but also in placenta. In vitro, Foxp3 and its transcription regulatory signalling molecules, including P‐Smad2, P‐Smad3 and Smad4, were diminished as well. Inhibition on Foxp3 expression was partially reversed by overexpression of Smad2 and Smad4. In FGR patients, Western blot results revealed that Foxp3, P‐Smad2, P‐Smad3 and Smad4 expression was inhibited in placenta. Our preliminary result suggests that maternal‐foetal immune tolerance mediated by Tregs plays an essential role in the development of FGR. The inhibited expression of Foxp3 and down‐regulated Smad2/Smad3/Smad4 signalling pathway were involved in the FGR pathogenesis. Targeting maternal‐foetal immune tolerance through Tregs might represent a novel therapeutic option for FGR.